The Impact of the Educational Counselor in Promoting Student Achievement Level in Government Schools at Irbid Governorate from School Principal Perspective - Aljarrah, Fatima Nasser (Journal of Ecohumanism, 2024)
One of the purposes and objectives of this research is to identify and assess the impact of the effectiveness of a school counselor on the academic success of students-an effectiveness that is manifested through the provision of academic, psychosocial, and vocational support to students, as well as through the facilitation of the interactions among students, teachers, and parents. In order to accomplish this study, the opinions of 180 public school principals were sought, and they were selected randomly to allow unbiased and generalizable interpretations of the principals in the governorate of Irbid to be the research population. A survey method was employed for data collection, and it consisted of a survey specifically designed for this research study, which contained several paragraphs related to the primary areas of the school counselor's role, as listed above. The responses collected were analyzed by establishing the means and the standard deviations. This research aimed to understand better the significant contribution that school counselors can offer in enhancing the educational process and academic progress within public schools in Irbid. It also confirmed that the multi-faceted support that they provide is essential. Results. In the study evaluating the role of the educational counselor within the scope of the public schools of Irbid, the results of which have been collected from school principals, the work provides a positive evaluation of the perceived influence of the counselors in terms of students' academic achievement across four primary dimensions: academic support that had a mean of 4.2 and a standard deviation of 0.8; psychological support with a mean of 4.0 and standard deviation of 0.9; vocational guidance with a mean of 3.8 and a standard deviation of 0.7; and interaction with parents and teachers with a mean of 4.1 and a standard deviation of 0.6. Such results reveal a high appreciation of the importance of the role of the educational counselor in improving the educational environment and the comprehensive support for the student as the role of the counselor has been exposed as a practical element in supporting the student academically and psychologically, guiding the student professionally, and in addition promoting effective communication between the school and the family.